A high-wear-resistance anti-corrosion castable for gooseneck pipe and a preparation method thereof

CN118955158BActive Publication Date: 2026-10-27HUZHOU CHANGXING XINGYING NEW TYPE REFRACTORY CONSTR MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411173204.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-26
Publication Date
2026-10-27
Estimated Expiration
2044-08-26

AI Technical Summary

Technical Problem

[0006]本发明是为了克服现有技术中鹅颈管耐火浇注料抗热震性能差、抗腐蚀性能差、易爆裂的缺陷,提供了一种鹅颈管用高耐磨防腐蚀浇注料及其制备方法以克服上述缺陷

Benefits of technology

(1)本发明使用醚基聚羧酸和柠檬酸钙作为高效分散剂,提高分散效果,从而提高浇注料的强度和耐久性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application belongs to the technical field of refractory materials, and particularly relates to a high-wear-resistance and corrosion-resistant castable for goose neck pipes and a preparation method thereof, which comprises, in percentage by weight, greater than or equal to 75% of refractory aggregate, 12% to 22% of refractory powder, 2.3% to 9% of oxide micro powder, 0.1% to 0.5% of corrosion inhibitor, 0.1% to 0.12% of high-efficiency dispersant and 0.3% to 0.6% of anti-explosion agent, wherein the high-efficiency dispersant uses calcium citrate and ether-based polycarboxylic acid ester, and the mass ratio of the two is 1: (2-5). Compared with traditional refractory materials, the high-wear-resistance and corrosion-resistant castable for goose neck pipes has more excellent wear resistance and thermal shock resistance, significantly improved anti-explosion property, and good corrosion resistance, and can better adapt to complex working conditions in goose neck pipes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of refractory materials technology, specifically relating to a high wear-resistant and corrosion-resistant castable for gooseneck tubes and its preparation method. Background Technology

[0002] The gooseneck tube, located at the top of the precalciner in a cement kiln, serves as the passage for suspended, high-temperature materials to pass through the precalciner and into the fifth-stage cyclone separator. The material then enters the rotary kiln via the fifth-stage cyclone separator. Raw materials undergo precalcination in the precalciner at temperatures reaching approximately 1200℃. A portion of the decomposed raw material enters the fifth-stage cyclone separator through the gooseneck tube at the top of the precalciner. Therefore, the refractory material of the gooseneck tube must withstand long-term high-temperature thermal shock, wind erosion, and acid / alkali corrosion. Thus, developing gooseneck tubes with thermal shock resistance, corrosion resistance, and wear resistance is crucial for the normal operation of cement kilns.

[0003] Compared to shaped refractory products, unshaped refractory materials, represented by refractory castables, have advantages such as shorter processing flow, lower production energy consumption and cost, ease of use, wide applicability, and better integrity and performance. Appropriately increasing the content of refractory aggregates in refractory castables can improve their refractoriness and abrasion resistance. Furthermore, adding active micro-powders such as calcined alumina, activated alumina, and silica fume can improve their physical properties at room temperature and high temperature, meeting application requirements. However, this also leads to problems such as a denser structure, smaller pore size, and narrower pore size distribution in the refractory castables, resulting in drawbacks such as longer baking times and poorer resistance to cracking.

[0004] The technical solution in patent CN202111598583.9 uses bauxite, silicon carbide, silicon micro powder, α-Al2O3 micro powder, andalusite micro powder, corundum powder, and an explosion retardant. It also involves low-temperature baking of the castable and drilling holes in the castable to ensure that the final castable has significant thermal shock resistance, corrosion resistance, wear resistance, and explosion retardancy.

[0005] However, this scheme has drawbacks. As the refractory aggregate content increases, more water is required during preparation. The addition of active micro-powders such as silica fume results in a denser structure in the castable, leading to poor physical properties, especially its anti-blast resistance. Furthermore, the poor uniformity of the natural bauxite raw material used in this scheme affects the stability of the refractory castable's performance indicators. The abrasion resistance, crack resistance, and resistance to sulfate compounds are all poor, making it difficult to adapt to the harsh working environment of cement kiln gooseneck tubes. Summary of the Invention

[0006] The present invention aims to overcome the defects of existing gooseneck tube refractory castables, such as poor thermal shock resistance, poor corrosion resistance, and easy cracking, and provides a high wear-resistant and corrosion-resistant castable for gooseneck tubes and its preparation method to overcome the above defects.

[0007] To achieve the objectives of the invention described above, the present invention is implemented through the following technical solution: A high wear-resistant and corrosion-resistant castable for gooseneck tubes, comprising the following components by weight percentage: It includes ≥75% refractory aggregate, 12%-22% refractory powder, 2.3%-9% oxide micro powder, 0.1%-0.5% corrosion inhibitor, 0.1%-0.12% high-efficiency dispersant and 0.3%-0.6% explosion retardant; the high-efficiency dispersant is selected from calcium citrate and ether-based polycarboxylate, with a mass ratio of 1:(2-5).

[0008] Compared to other components of a cement kiln, the factors limiting the lifespan of gooseneck tube refractory materials are: firstly, gooseneck tubes must withstand long-term high-temperature thermal shock, requiring high thermal shock resistance and wear resistance in the refractory materials; secondly, the exposed metal tubes are easily affected by external factors, leading to rapid cooling near the shell while the temperature remains relatively constant further away, resulting in a large internal temperature difference in the castable, which can easily cause cracking, leading to high-temperature detachment and burn-off of the gooseneck tube refractory material; and thirdly, the gooseneck tube is filled with a high-temperature moving solid alkaline medium, and with the application of co-processing in cement kilns, sulfides generated from the combustion of solid waste enter the gooseneck tube, making its chemical environment more complex.

[0009] In refractory materials, refractory aggregates are a major component of castables, typically accounting for 68%-72%. This invention increases the amount of refractory aggregates to over 75%, thereby improving the compressive and flexural strength of the castables and enabling them to maintain good structural stability at high temperatures. Due to the relatively lower content of refractory powder, this invention also incorporates oxide micro-powders, which can adjust the spacing between aggregates, fill micropores, improve flowability, and enhance refractoriness and bonding strength.

[0010] Generally, as the refractory aggregate content increases, the water content needs to be increased to maintain the flowability and plasticity of the castable. However, excessive water can lead to excessive internal stress during the baking process, resulting in a decrease in the strength of the castable. Therefore, for refractory castables with high refractory aggregate content and containing micropowder, it is necessary to find more suitable and efficient dispersants or water-reducing agents.

[0011] The high-efficiency dispersant in this invention includes ether-based polycarboxylate and calcium citrate. Ether-based polycarboxylate is a polymer formed by grafting polyethylene glycol side chains onto an anionic backbone. It can adsorb onto the surface of negatively charged silica particles, forming a dense adsorption layer on the particle surface. This effectively reduces the surface energy between particles, thereby reducing mutual attraction and agglomeration. Through electrostatic interaction and the effect of non-adsorbent side chains, this anti-flocculation effect is very significant, allowing for the uniform dispersion of refractory aggregates, refractory powders, and anti-explosion agents in the castable, thus improving the strength and durability of the castable. However, when the content of micro-powder in the castable exceeds 4%, the micro-powder particles are coated by the nonionic side chains of the ether-based polycarboxylate, leading to flocculation between the micro-powder and cement particles. This significantly reduces the dispersion effect of the ether-based polycarboxylate, resulting in poor dispersion of the ether-based polycarboxylate in refractory castables incorporating micro-powder.

[0012] Practice has shown that adding a certain amount of calcium citrate to castables containing ultrafine powder improves the fluidity of the castable compared to before addition, and the dispersion effect is significantly improved when added together with ether-based polycarboxylate. It is speculated that the active groups of calcium citrate adsorb onto the ultrafine powder, releasing the ether-based polycarboxylate bound to the powder. This allows the ether-based polycarboxylate to form a separation layer with the cement particles, thereby improving the overall fluidity of the castable. Further practice has shown that as the amount of calcium citrate added increases, the castable exhibits good fluidity when the mass ratio of calcium citrate to ether-based polycarboxylate is between 1:2 and 1:5. However, further addition of calcium citrate decreases the fluidity of the castable.

[0013] Generally, to improve the anti-burst properties of castables, microcracks are artificially created on the castable through physical or chemical methods, or pore openings are performed. This increases the contact area between the castable and sulfur-alkali compounds, making it easier for frequent redox reactions to occur on the castable, leading to expansion and contraction and eventually bursting. Compared to traditional dispersants, especially sodium citrate, calcium citrate and ether-based polycarboxylic acids exhibit significantly improved sulfur-alkali resistance, effectively addressing the castable bursting problem caused by sulfur-alkali compounds.

[0014] Preferably, the refractory powder includes grade I bauxite and high-alumina bauxite clinker in a mass ratio of 1:(2-3). Iron removal treatment removes iron impurities from the bauxite, improving its purity. Grade I bauxite typically possesses high quality and purity, while high-alumina bauxite clinker, after high-temperature calcination, can achieve a refractoriness exceeding 1750℃, exhibiting excellent high-temperature performance and corrosion resistance.

[0015] Preferably, the fineness of the primary bauxite and high-alumina bauxite clinker is 150-250 mesh and 300-350 mesh, respectively. Mixing the two types of bauxite powder with different mesh sizes allows for a more compact packing structure, thus increasing the bulk density. Furthermore, if the bauxite particle size is too uniform, stratification is likely to occur. Mixing two types of bauxite powder can reduce this stratification and improve the uniformity and stability of the castable.

[0016] Preferably, the refractory powder also includes mullite powder with a fineness between 200-325 mesh. Mullite has a high melting point, typically between 1810 and 1850°C, and the addition of high-grade mullite powder can effectively improve the refractoriness of the castable. Furthermore, mullite not only possesses high hardness and wear resistance but also good chemical stability and corrosion resistance. The addition of mullite powder to the castable can significantly improve the material's refractoriness, corrosion resistance, hardness, and wear resistance, among other properties. Preferably, the oxide powder includes one or more of the following: silicon powder, alumina powder, andalusite powder, and corundum powder.

[0017] Preferably, the explosion-proof agent comprises one or more combinations of aluminum powder, azoamide, and aluminum lactate. Aluminum powder acts as a reducing agent for the reduction of metal oxides, simultaneously generating bubbles and releasing hydrogen, displacing air, and undergoing re-oxidation under residual heat. Azoamide can, to some extent, alleviate the cracking phenomenon caused by internal stress concentration during the baking process of the castable. The addition of aluminum lactate to the castable causes matrix gelation and the formation of tortoise-shell cracks during curing, improving the air permeability of the castable.

[0018] Preferably, the refractory aggregate has a particle size of ≤10mm. When constructing thinner linings, using smaller particle size aggregates can reduce construction difficulties and performance degradation caused by excessively large aggregate particles.

[0019] Preferably, the corrosion inhibitor is an aminosilane coupling agent. Silane coupling agents are a class of organosilicon compounds with a special structure, typically containing one or more silane groups and an organic functional group. When the aminosilane coupling agent is added to the casting material of the present invention, due to the addition of an organic dispersant, the silane groups react chemically with the hydroxyl groups or other active groups on the surface of the inorganic material to form covalent bonds, while the amino-containing organic functional group is compatible with the organic material. This bridging effect significantly enhances the interfacial adhesion between the inorganic and organic materials, reduces interfacial defects, and thus improves the overall corrosion resistance of the material.

[0020] A baking and shaping method for a high wear-resistant and corrosion-resistant castable for gooseneck tubes, characterized by comprising the following steps in sequence: S1. Add refractory aggregate, refractory powder, oxide micro powder, corrosion inhibitor, high-efficiency dispersant, explosion retardant, and water to the mixer, and apply the resulting castable to the construction area. S2. Drill holes in the already coated and poured casting material to obtain open-hole casting material; S3. Perform a low-temperature baking operation on the perforated castable, with a baking temperature of 400-600℃, to obtain the final shaped castable.

[0021] As a further preferred embodiment, during the intermittent low-temperature baking operation in step S3, each baking session lasts for 3-6 minutes, and each baking pause lasts for 5-10 minutes. This invention employs a low-temperature intermittent baking method. Low-temperature intermittent baking helps moisture to gradually and fully evaporate during the baking process, preventing excessive stress inside the castable due to rapid moisture evaporation, which could cause cracking or spalling. Furthermore, intermittent baking induces micro-cracks in the castable, improving its anti-cracking performance.

[0022] Therefore, the present invention has the following beneficial effects: (1) The present invention uses ether-based polycarboxylic acid and calcium citrate as highly efficient dispersants to improve the dispersion effect, thereby improving the strength and durability of the castable.

[0023] (2) The present invention uses ether-based polycarboxylic acid and calcium citrate as highly efficient dispersants, so that the prepared castable has good anti-cracking properties and good tolerance to sulfuric acid compounds.

[0024] (3) By optimizing the selection and dosage of refractory aggregates and oxide powders, the overall wear resistance and corrosion resistance of castables can be improved. Detailed Implementation

[0025] The present invention will be further described below with reference to specific embodiments. Those skilled in the art will be able to implement the present invention based on these descriptions. Furthermore, the embodiments of the present invention described below are generally only some, not all, of the embodiments of the present invention. Therefore, all other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort should fall within the scope of protection of the present invention.

[0026] Example 1 A high wear-resistant and corrosion-resistant castable for gooseneck tubes, comprising, by weight percentage: 75% of the refractory aggregate is corundum with a particle size of ≤10mm and a three-graded distribution. 22% refractory powder, including 7% 150-mesh grade 1 bauxite and 15% 300-mesh high-alumina bauxite clinker; 2.4% oxide micro powder, including 1% silica micro powder, 1% andalusite micro powder, and 0.4% alumina micro powder; 0.1% of the corrosion inhibitor is γ-aminoethylaminopropyltrimethoxysilane; 0.1% of a highly efficient dispersant, including 0.03% calcium citrate and 0.07% ether-based polycarboxylate; 0.4% explosion retardant, including 0.2% aluminum powder and 0.2% azodicarbonamide.

[0027] Add the aforementioned refractory aggregates, refractory powders, oxide micro powders, corrosion inhibitors, high-efficiency dispersants, and explosion-proof agents to a mixer, along with water equivalent to 5% of the total mass, and mix to obtain a castable. Apply the mixed castable to the construction area. Then, perform a perforation operation on the coated castable, with a single perforation diameter of 5mm and a perforation density of 20 per m². 2 This yields the perforated castable refractory. The perforated castable is subjected to a low-temperature baking operation at a temperature of 400-420℃, with each baking session lasting 3 minutes and each baking pause lasting 5 minutes, to obtain the final shaped castable.

[0028] Example 2 A high wear-resistant and corrosion-resistant castable for gooseneck tubes, comprising, by weight percentage: 75% of the refractory aggregate is corundum with a particle size of ≤10mm and four-graded distribution. 15% refractory powder, which includes 4% by total mass of 250-mesh grade 1 bauxite and 10% of 359-mesh high-alumina bauxite clinker, and 1% of 200-225-mesh mullite powder. 9% oxide micro powder, including 2% silica micro powder, 2% andalusite micro powder, 2% alumina micro powder, and 2.5% corundum powder; 0.5% corrosion inhibitor, which is 3-aminopropyltriethoxysilane; 0.1% of a highly efficient dispersant, including 0.03% calcium citrate and 0.07% ether-based polycarboxylate; 0.4% explosion retardant, including 0.2% aluminum powder and 0.2% azodicarbonamide.

[0029] Add the aforementioned refractory aggregates, refractory powders, oxide micro powders, corrosion inhibitors, high-efficiency dispersants, and explosion-proof agents to a mixer, along with water equivalent to 5% of the total mass, and mix to obtain a castable. Apply the mixed castable to the construction area. Then, perform a perforation operation on the coated castable, with a single perforation diameter of 5mm and a perforation density of 20 per m². 2 This yields the perforated castable refractory. The perforated castable is subjected to a low-temperature baking operation at a temperature of 580-600℃, with each baking session lasting 6 minutes and each baking pause lasting 10 minutes, to obtain the final shaped castable.

[0030] Example 3 A high wear-resistant and corrosion-resistant castable for gooseneck tubes, comprising, by weight percentage: 80% of the refractory aggregate is selected from corundum with a particle size of ≤10mm in a three-graded manner; 17% refractory powder, including 5% 200-mesh grade 1 bauxite and 12% 350-mesh high-alumina bauxite clinker; 2.3% oxide micro powder, including 1% silica micro powder, 1% andalusite micro powder, and 0.3% alumina micro powder; 0.1% of the corrosion inhibitor is γ-aminopropyltrimethoxysilane; 0.12% of a highly efficient dispersant, including 0.02% calcium citrate and 0.1% ether-based polycarboxylate; 0.48% explosion retardant, including 0.2% aluminum powder, 0.2% azoamide, and 0.08% aluminum lactate.

[0031] Add the aforementioned refractory aggregates, refractory powders, oxide micro powders, corrosion inhibitors, high-efficiency dispersants, and explosion-proof agents to a mixer, along with water equivalent to 5% of the total mass, and mix to obtain a castable. Apply the mixed castable to the construction area. Then, perform a perforation operation on the coated castable, with a single perforation diameter of 5mm and a perforation density of 20 per m². 2 This yields the perforated castable refractory. The perforated castable is subjected to a low-temperature baking operation at a temperature of 400-420℃, with each baking session lasting 3 minutes and each baking pause lasting 5 minutes, to obtain the final shaped castable.

[0032] Example 4 A high wear-resistant and corrosion-resistant castable for gooseneck tubes, comprising, by weight percentage: 82% of the refractory aggregate is corundum with a particle size of ≤10mm and a three-graded distribution. 15% refractory powder, including 5% 250-mesh grade 1 bauxite and 10% 350-mesh high-alumina bauxite clinker; 2.4% oxide micro powder, including 1% silica micro powder, 1% andalusite micro powder, and 0.4% alumina micro powder; 0.1% of the corrosion inhibitor is γ-aminoethylaminopropyltrimethoxysilane; 0.1% high-efficiency dispersant, including 0.03% calcium citrate and 0.07% ether-based polycarboxylate; 0.4% explosion retardant, including 0.2% aluminum powder and 0.2% azodicarbonamide.

[0033] Add the aforementioned refractory aggregates, refractory powders, oxide micro powders, corrosion inhibitors, high-efficiency dispersants, and explosion-proof agents to a mixer, along with water equivalent to 5% of the total mass, and mix to obtain a castable. Apply the mixed castable to the construction area. Then, perform a perforation operation on the coated castable, with a single perforation diameter of 5mm and a perforation density of 20 per m². 2 This yields the perforated castable refractory. The perforated castable is subjected to a low-temperature baking operation at a temperature of 580-600℃, with each baking session lasting 3 minutes and each baking pause lasting 5 minutes, to obtain the final shaped castable.

[0034] Example 5 A high wear-resistant and corrosion-resistant castable for gooseneck tubes, comprising, by weight percentage: 82% of the refractory aggregate is corundum with a particle size of ≤10mm and a three-graded distribution. 12% refractory powder, which includes 3% 250-mesh grade 1 bauxite and 9% 350-mesh high-alumina bauxite clinker; 5.2% oxide micro powder, including 1.2% silica micro powder, 1.2% andalusite micro powder, 1.2% alumina micro powder, and 1.6% corundum powder; 0.1% of the corrosion inhibitor is γ-aminoethylaminopropyltrimethoxysilane; 0.1% of a highly efficient dispersant, including 0.02% calcium citrate and 0.08% ether-based polycarboxylate; 0.6% explosion retardant, including 0.2% aluminum powder, 0.2% azoamide, and 0.2% aluminum lactate.

[0035] Add the aforementioned refractory aggregates, refractory powders, oxide micro powders, corrosion inhibitors, high-efficiency dispersants, and explosion-proof agents to a mixer, along with water equivalent to 5% of the total mass, and mix to obtain a castable. Apply the mixed castable to the construction area. Then, perform a perforation operation on the coated castable, with a single perforation diameter of 5mm and a perforation density of 20 per m². 2 This yields the perforated castable refractory. The perforated castable is subjected to a low-temperature baking operation at a temperature of 580-600℃, with each baking session lasting 4 minutes and each baking pause lasting 8 minutes, to obtain the final shaped castable.

[0036] To verify the effects of the particle size distribution and the selection of high-efficiency dispersant on the performance of castables, the following comparative experiments were conducted. The preparation methods of the castables in each comparative example were all in accordance with the preparation method of Example 5, and will not be repeated here.

[0037] Comparative Example 1 A refractory castable, comprising, by weight percentage: 68% of the refractory aggregate is corundum with a particle size of ≤10mm and a three-graded distribution. 29% refractory powder, including 9% 200-mesh grade 1 bauxite and 20% 350-mesh high-alumina bauxite clinker; 2.3% oxide micro powder, including 1% silica micro powder, 1% andalusite micro powder, and 0.3% alumina micro powder; 0.1% of the corrosion inhibitor is γ-aminoethylaminopropyltrimethoxysilane; 0.6% explosion retardant, including 0.25% aluminum powder, 0.25% azoamide, and 0.1% aluminum lactate.

[0038] Comparative Example 2 A refractory castable, comprising, by weight percentage: 80% of the refractory aggregate is selected from corundum with a particle size of ≤10mm in a three-graded manner; 17% refractory powder, including 5% 200-mesh grade 1 bauxite and 12% 350-mesh high-alumina bauxite clinker; 2.3% oxide micro powder, including 1% silica micro powder, 1% andalusite micro powder, and 0.3% alumina micro powder; 0.1% of the corrosion inhibitor is γ-aminoethylaminopropyltrimethoxysilane; 0.6% explosion retardant, including 0.25% aluminum powder, 0.25% azoamide, and 0.1% aluminum lactate.

[0039] Comparative Example 3 A refractory castable, comprising, by weight percentage: 82% of the refractory aggregate is corundum with a particle size of ≤10mm and a three-graded distribution. 16.3% refractory powder, including 4.1% 250-mesh grade 1 bauxite and 12.2% 350-mesh high-alumina bauxite clinker; 1% oxide micro powder, which includes 0.25% silica micro powder, 0.25% andalusite micro powder, 0.25% alumina micro powder, and 0.25% corundum powder; 0.1% of the corrosion inhibitor is γ-aminoethylaminopropyltrimethoxysilane; 0.1% of a highly efficient dispersant, which is an ether-based polycarboxylic acid ester; 0.5% explosion retardant, including 0.2% aluminum powder, 0.2% azoamide, and 0.1% aluminum lactate.

[0040] Comparative Example 4 A refractory castable, comprising, by weight percentage: 82% of the refractory aggregate is corundum with a particle size of ≤10mm and a three-graded distribution. 12% refractory powder, which includes 3% 250-mesh grade 1 bauxite and 9% 350-mesh high-alumina bauxite clinker; 5.3% oxide micro powder, including 1.2% silica micro powder, 1.2% andalusite micro powder, 1.2% alumina micro powder, and 1.7% corundum powder; 0.1% of the corrosion inhibitor is γ-aminoethylaminopropyltrimethoxysilane; 0.1% of a highly efficient dispersant, which is an ether-based polycarboxylic acid ester; 0.5% explosion retardant, including 0.2% aluminum powder, 0.2% azoamide, and 0.1% aluminum lactate.

[0041] Comparative Example 5 A refractory castable, comprising, by weight percentage: 82% of the refractory aggregate is corundum with a particle size of ≤10mm and a three-graded distribution. 12% refractory powder, which includes 3% 250-mesh grade 1 bauxite and 9% 350-mesh high-alumina bauxite clinker; 5.3% oxide micro powder, including 1.2% silica micro powder, 1.2% andalusite micro powder, 1.2% alumina micro powder, and 1.7% corundum powder; 0.1% of the corrosion inhibitor is γ-aminoethylaminopropyltrimethoxysilane; 0.05% of a highly efficient dispersant, including 0.01% calcium citrate and 0.04% ether-based polycarboxylate; 0.55% explosion retardant, including 0.22% aluminum powder, 0.22% azoamide, and 0.11% aluminum lactate.

[0042] Comparative Example 6 A refractory castable, comprising, by weight percentage: 82% of the refractory aggregate is corundum with a particle size of ≤10mm and a three-graded distribution. 12% refractory powder, which includes 3% 250-mesh grade 1 bauxite and 9% 350-mesh high-alumina bauxite clinker; 5.2% oxide micro powder, including 1.2% silica micro powder, 1.2% andalusite micro powder, 1.2% alumina micro powder, and 1.6% corundum powder; 0.1% of the corrosion inhibitor is γ-aminoethylaminopropyltrimethoxysilane; 0.2% of a highly efficient dispersant, including 0.04% calcium citrate and 0.16% ether-based polycarboxylate; 0.5% explosion retardant, including 0.2% aluminum powder, 0.2% azoamide, and 0.1% aluminum lactate.

[0043] Comparative Example 7 A refractory castable, comprising, by weight percentage: 82% of the refractory aggregate is corundum with a particle size of ≤10mm and a three-graded distribution. 12% refractory powder, which includes 3% 250-mesh grade 1 bauxite and 9% 350-mesh high-alumina bauxite clinker; 5.3% oxide micro powder, including 1% silica micro powder, 1% andalusite micro powder, 1% alumina micro powder, and 1.3% corundum powder; 0.1% of the corrosion inhibitor is γ-aminoethylaminopropyltrimethoxysilane; 0.1% high-efficiency dispersant, including 0.05% calcium citrate and 0.05% ether-based polycarboxylate; 0.5% explosion retardant, including 0.2% aluminum powder, 0.2% azoamide, and 0.1% aluminum lactate.

[0044] Comparative Example 8 A refractory castable, comprising, by weight percentage: 82% of the refractory aggregate is corundum with a particle size of ≤10mm and a three-graded distribution. 12% refractory powder, which includes 3% 250-mesh grade 1 bauxite and 9% 350-mesh high-alumina bauxite clinker; 5.3% oxide micro powder, including 1% silica micro powder, 1% andalusite micro powder, 1% alumina micro powder, and 1.3% corundum powder; 0.1% of the corrosion inhibitor is γ-aminoethylaminopropyltrimethoxysilane; 0.1% high-efficiency dispersant, including 0.01% calcium citrate and 0.09% ether-based polycarboxylate; 0.5% explosion retardant, including 0.2% aluminum powder, 0.2% azoamide, and 0.1% aluminum lactate.

[0045] Comparative Example 9 A high wear-resistant and corrosion-resistant castable for gooseneck tubes, comprising, by weight percentage: 82% of the refractory aggregate is corundum with a particle size of ≤10mm and a three-graded distribution. 12% refractory powder, which includes 3% 250-mesh grade 1 bauxite and 9% 350-mesh high-alumina bauxite clinker; 5.3% oxide micro powder, including 1.2% silica micro powder, 1.2% andalusite micro powder, 1.2% alumina micro powder, and 1.7% corundum powder; 0.1% of the corrosion inhibitor is γ-aminoethylaminopropyltrimethoxysilane; 0.1% of a highly efficient dispersant, including 0.02% sodium citrate and 0.08% ether-based polycarboxylate; 0.5% explosion retardant, including 0.2% aluminum powder, 0.2% azoamide, and 0.1% aluminum lactate.

[0046] Physical properties were tested according to GB / T4513.6-2017, and acid resistance was tested according to GB / T17601-2008. Table 1 shows the performance test results for Examples 1-5. Table 2 shows the performance test results for comparative examples 1 to 9. As shown in Tables 1 and 2 above, the refractory castables in Examples 1-5 of this invention exhibit significant advantages in terms of flexural strength, compressive strength, sulfuric acid erosion resistance, and room temperature abrasion. Compared to Comparative Example 1, the compressive strength, flexural strength, and abrasion resistance of castables with lower refractory aggregate content are far inferior to those with higher aggregate content. Compared to Comparative Example 2, the lack of dispersant in castables with a refractory aggregate content greater than 75% results in poor flowability. In this case, more water must be added to complete the coating, severely impacting the material properties of the castable. Compared to Comparative Example 3, ether-based polycarboxylate provides excellent dispersion in castables with a micropowder content less than 4%, significantly reducing the required water volume. However, due to the lack of sufficient microparticles to fill the voids, the castable mixture struggles to achieve maximum bulk density. Compared to Comparative Example 4, the dispersion effect of ether-based polycarboxylate is very limited in castables with a micropowder content greater than 4%. Compared to Comparative Example 5, the dispersion effect of ether-based polycarboxylate was somewhat restored after adding a small amount of the combined dispersant of calcium citrate and ether-based polycarboxylate. Compared to Comparative Example 6, excessive amounts of the combined dispersant of calcium citrate and ether-based polycarboxylate interfered with the hydration reaction of the castable, affecting the material strength. Compared to Comparative Examples 7 and 8, when the proportion of calcium citrate added was too small, the improvement effect on the performance of the castable was limited; when excessive amounts of calcium citrate were added, the overall dispersion effect of the dispersant decreased. Compared to Comparative Example 9, the traditional sodium citrate dispersant had poor corrosion resistance, while the combined dispersant of calcium citrate and ether-based polycarboxylate had significant advantages in improving the compressive and flexural strength, abrasion resistance, and corrosion resistance of the castable.

Claims

1. A high wear-resistant and corrosion-resistant castable for gooseneck tubes, characterized in that: Calculated by weight percentage, it consists of ≥75% refractory aggregate, 12%-22% refractory powder, 2.3%-9% oxide micro powder, 0.1%-0.5% corrosion inhibitor, 0.1%-0.12% high-efficiency dispersant, and 0.3%-0.6% explosion retardant, totaling 100%. The high-efficiency dispersant comprises calcium citrate and ether-based polycarboxylic acid ester, with a mass ratio of 1:(2-5). The refractory powder includes grade 1 bauxite and high-alumina bauxite clinker, with a mass ratio of 1:(2-3). The oxide powder includes one or more of the following: silicon powder, alumina powder, andalusite powder, and corundum powder. The explosion-proof agent includes one or more of aluminum powder, azoamide, and aluminum lactate; The refractory aggregate is corundum with a particle size ≤10mm; The corrosion inhibitor is an aminosilane coupling agent.

2. The high wear-resistant and corrosion-resistant castable for gooseneck pipes according to claim 1, characterized in that: The fineness of the first-grade bauxite and the high-alumina bauxite clinker are 150-250 mesh and 300-350 mesh, respectively.

3. The high wear-resistant and corrosion-resistant castable for gooseneck pipes according to claim 1, characterized in that: The refractory powder also includes mullite powder with a fineness of 200-225 mesh.

4. A baking and shaping method for a high wear-resistant and corrosion-resistant castable for gooseneck tubes as described in any one of claims 1-3, characterized in that... The steps are as follows: S1. Add refractory aggregate, refractory powder, oxide micro powder, corrosion inhibitor, high-efficiency dispersant, explosion retardant, and water to a mixer and mix to obtain a castable. Apply the mixed castable to the construction area. S2. Drill holes in the already coated and poured casting material to obtain open-hole casting material; S3. Perform a low-temperature baking operation on the perforated castable, with a baking temperature of 400-600℃, to obtain the final shaped castable.

5. The baking and shaping method for a high wear-resistant and corrosion-resistant castable for gooseneck tubes according to claim 4, characterized in that: In step S3, an intermittent low-temperature baking operation is performed, with each baking session lasting 3-6 minutes and each baking pause lasting 5-10 minutes.

Citation Information

Patent Citations

  • A thermal shock resistant, corrosion resistant, and wear-resistant castable for gooseneck tubes of decomposers.

    CN114105618B

  • Corundum-mullite gel composite wear-resistant castable and baking and shaping method thereof

    CN113636851A

  • Thermal-shock-resistant anti-corrosion wear-resistant castable for gooseneck pipe of decomposing furnace

    CN114105618A